Community changes in a restored tussock sedge wetland over 15 years: Expansion and competition - Xianglong Xing; Qing Qi; Shouzheng Tong; Yu An; Heshan Ni; Yuan Xin; Mingye Zhang; Dongjie Zhang; Walian Du (Global Ecology and Conservation)
Vegetation restoration is one of the most effective means to reestablish wetlands. However, little is known about how plant communities expand and compete after wetland restoration because of the dearth of data from long-term monitoring. In this study, we monitored a restored Carex tussock wetland over a 15-year period, assessed the extent of Carex tussock expansion, analyzed the effects of interspecific competition and environmental factors on Carex tussock growth, and explored the driving mechanisms of the expansion of Carex tussock community. Our results demonstrate that the Carex tussock community continued its outward dispersal after restoration, with a total expansion area of 770 m2. The ecological characteristics and species diversity in the restoration area were higher than those in the expansion area. Additionally, both the density and biodiversity of Carex tussock in the restoration area decreased with the age of the restoration. Experiments indicated that competition and water level significantly influenced the growth of Carex tussock and Carex exhibited weaker competitiveness in a mixed constructure model. The structural equation model revealed that topography was the primary driver of Carex tussock expansion. The priority effect of Carex dispersal mitigated the impact of competition on expansion. This study offers new insights for future wetland restoration practices, particularly concerning Carex tussock ecosystems.